The evolution of antibiotic resistance in bacterial colonies - Frost, I (2017)
The continuing rise of antibiotic resistance is threatening a return to the world of pre-antibiotic medicine. Multi-drug resistant pathogens are already claiming lives and causing economic losses in developing and developed countries alike. We need, therefore, to understand what allows resistant strains to spread; what makes them evolutionarily competitive in and amongst other strains and species. The majority of laboratory studies of antibiotic resistance focus on simple growth in liquid culture. By contrast, microbes commonly grow as surface-associated communities, in which interactions between neighbouring cells have strong consequences for competition and evolution. My first goal was to understand how growth in such environments affects the success of a resistant strain. By competing an antibiotic resistant and susceptible strain of the pathogenic bacterium Pseudomonas aeruginosa, I found that growth in dense colonies on agar allowed a resistant strain to protect susceptible strains, to the extent that the susceptible strain may even prevail under antibiotic treatment. This effect was specific to a cooperative mechanism of antibiotic resistance, however; a β-lactamase enzyme that digests the antibiotics surrounding a resistant cell. A further, unexpected reason that susceptible cells could prevail was that they elongate under antibiotic treatment, allowing them to push shorter resistant cells aside in the competition for the growing edge of a colony. My work suggests that the rise of cooperative resistance mechanisms should be more easily suppressed than for non-social mechanisms. However, one major strategy to overcome antibiotic resistance is the use of antibiotic-adjuvants, drugs which inhibit a mechanism of antibiotic resistance. It is not clear if these adjuvants will tend to suppress or promote cooperative resistance mechanisms. I performed experiments to test the effects of inhibitory adjuvants on cooperative resistance. These revealed that the effects of adjuvants are varied. In liquid culture, an adjuvant inhibited resistance evolution, while, in colony experiments, it promoted resistance evolution by removing the cross protection of susceptible strains. Given the complexity and importance of antibiotic adjuvants, I developed an eco-evolutionary model to dissect these complexities associated with the combination of interacting microbial and molecular species. As in my experiments, the models identified conditions where an inhibitory adjuvant can increase selection for resistance. However, the theory also identifies scenarios for which adjuvants will delay resistance evolution by shutting down the associated evolutionary pathway. Broadening the modelling framework to include the stochastic effects of rare mutation, I found that early administration of adjuvant inhibitors can be a powerful way to suppress the emergence of antibiotic resistance. Microbial interactions are complex and affected by the growth environment. My thesis underlines that the study of antibiotic resistance will benefit from greater consideration of how bacteria interact and, more broadly, how their ecology and evolution determine the rise, or fall, of resistance.